A história pré-colonial em Vista Alegre do Prata/RS - Pedron, Valéria (2020)
Bearing in mind that “the history of humanity was and is the constant contact between different social groups with conflicts, domination, assimilation and alliances according to the power of each one” (NASCIMENTO, 2013, p. 151), in recent decades, the history that surrounds the indigenous presence of Rio Grande do Sul, before the European immigration process, became a topic of constant debate: the importance of conserving an asset of equal significant value to the history of our own ancestors was realized. In this line of investigation, this research aims to analyze the indigenous presence in the current region of the municipality of Vista Alegre do Prata – RS, which took place in the so-called pre-colonial period, thus aiming to identify the ethnic groups that inhabited the place in analysis and its cultural, housing, political and social patterns.